2010
DOI: 10.1111/j.1365-2923.2010.03711.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of language family on academic performance in Year 1 and 2 MBBS students

Abstract: Our results confirmed that, overall, local students perform better academically than international students. However, given that language family differences exist, this may reflect acculturation rather than simply English language skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…In an Australian OSCE study with a specific focus on communication skills, both students of non-Western origin and students who did not have English as their mother tongue were found to perform poorer than their Western, English-speaking counterparts – especially in terms of assessed communication skills [7]. Moreover, Mann et al [9] reported poorer results of international students in first- and second-year OSCEs in an Australian Medical School – even in international students who had identified English as their language family. The authors, therefore, argued that it is possibly not the language acquisition in a foreign country itself that is a major predictor of academic performance, but rather international students’ acculturation [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an Australian OSCE study with a specific focus on communication skills, both students of non-Western origin and students who did not have English as their mother tongue were found to perform poorer than their Western, English-speaking counterparts – especially in terms of assessed communication skills [7]. Moreover, Mann et al [9] reported poorer results of international students in first- and second-year OSCEs in an Australian Medical School – even in international students who had identified English as their language family. The authors, therefore, argued that it is possibly not the language acquisition in a foreign country itself that is a major predictor of academic performance, but rather international students’ acculturation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Mann et al [9] reported poorer results of international students in first- and second-year OSCEs in an Australian Medical School – even in international students who had identified English as their language family. The authors, therefore, argued that it is possibly not the language acquisition in a foreign country itself that is a major predictor of academic performance, but rather international students’ acculturation [9]. However, to the best of our knowledge, so far, no studies have been conducted on international students’ OSCE performance either for non-English speaking countries or for the field of psychosocial medicine.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the fact of several international surveys that came to similar conclusions [14], [17], [18], [22] these results are hardly surprising on the one hand. On the other hand the present paper is the first survey of this kind for the German-speaking area.…”
Section: Discussionmentioning
confidence: 55%
“…And in a country like Germany again we find absolutely different structures. Reasons for the found performance distinctions could be due to linguistic differences to a large extent [22]. The German written tests may solely be multiple-choice-tests in which the right answer has to be detected passively only [23] but it can be expected that replying to many questions in a short time a native speaker is clearly superior to a non-native speaker because he can capture and understand the content of a question quicker and therefore has more time for answering it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation